Zakres poprawek Senatu - problemy teorii i praktyki: [Scope of Senate amendments - problems of theory and practice] (Studia Prawnicze / The Legal Studies, 2001)
Niniejszy artykuł jest próbą analizy problematyki poprawek Senatu. Podczas gdy inne aspekty funkcjonowania Senatu doczekały się już swojego całościowego opracowania, problem granic poprawek jest jeszcze stosunkowo mało znany1. A to właśnie on decyduje o faktycznym miejscu Senatu w systemie politycznym Rzeczypospolitej Polskiej. Wspomniany problem jest tym bardziej interesujący, że stanowi ściśle polski fenomen. Ustalona w Polsce interpretacja uprawnień Senatu w procesie ustawodawczym nie znajduje potwierdzenia zarówno w naszej, jak i w obcej praktyce parlamentarnej. Artykuł nie rości sobie prawa do całościowego przedstawienia niniejszego problemu, lecz stara się jedynie zaprezentować i zdefiniować najistotniejsze praktyczne problemy działalności Senatu, jakie powstają w związku z ustalonym w wyniku orzecznictwa Trybunału Konstytucyjnego zakresem poprawek Senatu. This article attempts to analyse the issue of Senate amendments. While other aspects of the Senate's functioning have already received their own comprehensive study, the problem of amendment boundaries is still relatively little known. And it is this that determines the actual place of the Senate in the political system of the Republic of Poland. The aforementioned problem is all the more interesting because it is strictly a Polish phenomenon. The established interpretation in Poland of the powers of the Senate in the legislative process is not borne out by both our and foreign parliamentary practice. This article does not claim to present the problem in its entirety, but merely seeks to present and define the most relevant practical problems of the Senate's activity that arise in connection with the scope of the Senate's amendments as determined by the Constitutional Court's case law.